TRIGEMINAL NEURALGIA CAUSED BY ARTERIOVENOUS MALFORMATION OF THE POSTERIOR FOSSA : A CASE REPORT - Widodo Mardi Santoso; Opik Jamaludin; Catur Ari Setianto; Neila Raisa (Journal of Pain, Headache and Vertigo, 2020)
Trigeminal neuralgia (TN) is a sudden, severe, brief, stabbing, and recurrent pain within one or more branches of the trigeminal nerve. Trigeminal neuralgia has a prevalence of 0.1-0.2 per thousand and an incidence ranging from about 4-5/100,000/year up to 20/100,000/year after age 60. A 35 year old woman presented with 1 year history of right facial pain. Physical examination showed hyperalgesia and allodynia in all division of right trigeminal nerve. Magnetic resonance imaging with contrast demonstrated flow void signal in the right cerebellopontine angle. Computed tomography angiography confirmed the diagnosis of AVM (arteriovenous malformation), and demonstrated the malformed niduses were fed by the right posterior inferior cerebellar artery and the right superior cerebellar artery, and drained vein into basal vein of rosenthal, without hemorrhage or aneurysm intranidal appearance. carbamazepin 2x100 mg per oral for 7 days effectively decreased the facial pain significantly (from the numeric rating scale (NRS) score 8 to 5). Open surgical was not prefered for this patient because the AVM was small, unruptured, and located in eloquent area. Radiosurgery is considered if the medication fails. Trigeminal neuralgia with facial pain affecting all devision of nervus trigeminus with pulsatile headache can be suspected symptomatic TN. Radiological examination such as Magnetic Resonance Imaging (MRI) and Computed Tomography (CT) angiography can be performed to detect the cause of TN.